The Influence Green Operations on Sustainability Performance Through Service Quality in Banking Services - Suparyadi, Hendra; Sulisytowati, Niken (IJOSMAS, 2025)
This study aims to find out and analyze the influence of Green Operations on Sustainability Performance through Service Quality in Banking Services. The population of this study is PT XYZ employees with a sample of 102 people. The technique used in the distribution of this questionnaire is purposive sampling. This technique is included in the category of non-probability sampling. The data analysis method used the Structural Equation Model-Partial Least Square (SEM-PLS). The results of the study show that Green Operations has a positive effect on Service Quality, Service Quality has a positive effect on Sustainability Performance, Green Operations has a positive and significant effect on Sustainability Performance, and there is an indirect influence of Green Operations on Sustainability Performance through Service Quality. This means that Service Quality acts as a partial mediating variable that strengthens the relationship between green operations and sustainability performance.